Surgical Intervention Strategies of Necrotizing Pancreatitis With Abdominal Compartment Syndrome. Issue 10 (November 2021) - Kao, Shih-Yi; Chen, Tien-Hua; Wang, Chien-Ying; Hsiao, Chen-Yuan; Chiang, Ching-Shu; Chou, Shu-Cheng; Chen, Jui-Yu; Tsai, Pei-Jiun
Abstract : Objective: Acute pancreatitis can usually recover after conservative treatment. Five to 10 percent of acute pancreatitis may proceed into peripancreatic fluid collection and necrosis development, called necrotizing pancreatitis (NP), which has a high mortality rate. If it is accompanied by the occurrence of abdominal compartment syndrome (ACS) and does not respond to medical therapy, surgical intervention is indicated. Methods: We analyzed our experience of surgical intervention strategies for NP patients with medically irreversible ACS from January 1, 2004, to December 31, 2018. Results: Of the 47 NP patients with ACS, mean Ranson score was 6.5, mean Acute Physiology and Chronic Health Evaluation II score was 22.2, and Modified computed tomography severity index score was all 8 or greater. The mean total postoperative hospital length of stay was 80.2 days, of which the mean intensive care unit length of stay was 16.6 days. The overall complication rate was 31.9%. The mortality rate was 8.5%. Among the 47 patients, only fungemia was significantly associated with mortality incidence. Conclusions: The combination of multiple drainage tube placement, feeding jejunostomy, and ileostomy at the same time were effective surgical intervention strategies for NP patients with ACS, which brought a lower mortality rate.